New records of Epidendrum (Orchidaceae) for Colombia: Epidendrum porphyreonocturnum Hágsater & R. Jiménez and Epidendrum whittenii Hágsater & Dodson - Perdomo, Oscar (2020)
We report for the first time for Colombia Epidendrum porphyreonocturnum Hágsater & R. Jiménez and Epidendrum whittenii Hágsater & Dodson, two species of orchids found in the Andean-Amazonian Foothills from the department of Caquetá. These species were previously known in Ecuador and Peru. Both species were categorized as Vulnerable according to IUCN criteria due to the menaces over their habitat and the low number of known populations. These records enrich the knowledge of the Colombian orchid flower and highlight the need to make greater efforts for the knowledge and conservation of the foothill.